2016
DOI: 10.1364/oe.24.020318
|View full text |Cite
|
Sign up to set email alerts
|

All-optical NRZ wavelength conversion based on a single hybrid III-V/Si SOA and optical filtering

Abstract: A six-channel wavelength-division-multiplexed optical transceiver with a compact footprint of 1.5 Â 0.65 mm 2 for off-chip and on-chip interconnects is demonstrated on a single silicon-on-insulator chip. An arrayed waveguide grating is used as the (de)multiplexer, and III-V electroabsorption sections fabricated by hybrid integration technology are used as both modulators and detectors, which also enable duplex links. The 30-Gb/s capacity for each of the six wavelength channels for the off-chip transceiver is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Micro-packaging solutions compatible with isolator integration have been developed for the hybrid integration of a laser with SiP chips 28 . Heterogeneous integration of the MLL 29 and the SOA 30 would also reduce reflections at the first interfaces, potentially allowing for implementation of the system with a single isolator at the output of the Tx. Hybrid integration is even more challenging for the SOA due to its two optical interfaces and is currently under development.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-packaging solutions compatible with isolator integration have been developed for the hybrid integration of a laser with SiP chips 28 . Heterogeneous integration of the MLL 29 and the SOA 30 would also reduce reflections at the first interfaces, potentially allowing for implementation of the system with a single isolator at the output of the Tx. Hybrid integration is even more challenging for the SOA due to its two optical interfaces and is currently under development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their results demonstrated that with the power consumption of the SOA being <250 mW, the converter could realize 6 pJ/bit energy consumption at 40 Gb/s. The hybrid integration method involves DVS-BCB bonding [86], as shown in Figure 13. In the same year, Komljenovic et al [20] from the University of California realized an tunable laser on low-loss silicon waveguide platforms with micro-ring resonators as the feedback component, as shown in Figure 12b.…”
Section: The Application Of Silicon-based Soasmentioning
confidence: 99%
“…Furthermore, their results demonstrated that with the power consumption of the SOA being <250 mW, the converter could realize 6 pJ/bit energy consumption at 40 Gb/s. The hybrid integration method involves DVS-BCB bonding [86], as shown in Figure 13.…”
Section: The Application Of Silicon-based Soasmentioning
confidence: 99%